(untitled) (Research, Society and Development, 2021)
The purpose was to describe the evaluation process and speech therapy intervention of a child with Turner Syndrome through a longitudinal case study. Documents filed in electronic medical records (history, diagnostic hypothesis, unique therapeutic plan and clinical evolution) referring to the assessment (3 sessions) and speech therapy (17 sessions) were analyzed. The initial assessment data showed deficits in general communication skills (emissive and receptive vocabulary), with a score lower than expected for their age group. With the speech therapy intervention, a significant evolution in these skills and an increase in the score found in the assessment was evidenced, demonstrating the importance of the speech therapist in the care of this population.